Representasi Self-Love dalam Lirik Lagu Monolog Karya Pamungkas (Analisis Semiotika Ferdinand de Saussure) - Zhafirah, Puteri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Music is one of the communication media that can convey various messages and meanings through song lyrics, including messages about the importance of self-love. The song “Monolog” by Pamungkas illustrates a process of self-reflection, acceptance of imperfections, and efforts to rise from emotional experiences. This study aims to identify the representation of self-love in the lyrics of the song “Monolog” by Pamungkas using Ferdinand de Saussure’s semiotic analysis. This research employs a qualitative descriptive approach with a semiotic analysis method focusing on the relationship between the signifier and the signified. The data were collected through documentation of the song lyrics and a literature review related to the research topic. The results of the study show that the lyrics of “Monolog” represent the concept of self-love through four main aspects: self-awareness, self-acceptance, self-compassion, and self-appreciation. These aspects are reflected through linguistic signs that indicate awareness of one’s condition, acceptance of personal feelings, the ability to treat oneself with understanding, and appreciation of life experiences and personal growth. Thus, the song “Monolog” not only represents sadness but also conveys a message about the importance of recognizing, accepting, understanding, and appreciating oneself as part of the process of emotional maturity.